Dynamics of submerged jet flow in a pipe in a longitudinal magnetic field - Listratov, Yaroslav Igorevich; Razuvanov, Nikita Georgiyevich; Belyaev, Ivan Aleksandrovich; Sviridov, Evgeny Valentinovich (Computational Continuum Mechanics, 2023)
A submerged jet flow of an electrically conductive liquid in a longitudinal uniform magnetic field is considered. The flow is formed by a sudden expansion of the flow from a hole into a pipe (with a diameter ratio of 1 to 5) filled with the same liquid at a constant flow rate. The study was carried out using the method of direct numerical simulation. The simulation results are compared with the averaged longitudinal velocity measurements obtained in the experiments on mercury. The Reynolds numbers correspond to the turbulent flow in the jet at the inlet and the laminar flow at the outlet of the pipe. In a moderate magnetic field, with an increase in the Hartmann number in the flow, turbulent transport is suppressed. The flow is largely laminarized up to the jet front, where, due to instability, it passes to turbulence. The effective length of the jet increases with increasing the Hartmann number, since the resulting electromagnetic force prevents the jet expansion. In strong magnetic fields, there is a tendency for the flow to be unstable due to the interaction of the formed secondary flows with the magnetic field. The radial components of the induced electric current arising in this case in the flow cause transverse stretching and compression of the jet profile by the electromagnetic force. Time-variable deformations of the jet profile and their spatial inhomogeneity in a magnetic field lead to the appearance of an ordered flow swirl. The swirl rate depends on the Hartmann number and, in the studied range of Reynolds numbers, does not exceed 12% of the average outlet flow rate. The development of instability is accompanied by time alternations of intervals in which the flow has significantly different amplitudes of velocity fluctuations.
Keywords: round jet; liquid metal; flow; longitudinal magnetic field; direct numerical simulation